Assessment of Genetic Variability and Character Association for Morpho-physiological and Quality Traits in Rice under Aerobic Conditions - Das, Ishwar; Kumar, Rakesh; Kesh, Hari; Sharma, Sudhir; Pilania, Prerna; Saini, Vishal; Amit, (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during kharif season (June–October, 2022) at Rice Research Station, Kaul, CCSHAU, Hisar using 48 rice genotypes to evaluate the genetic variability and character association under aerobic conditions. Analysis of variance revealed that the mean sum of squares was highly significant for all the traits examined. The magnitude of phenotypic coefficient of variation exceeded the genotypic coefficient of variation for all the traits analysed in the study. High genotypic coefficient of variation and phenotypic coefficient of variation were observed for root dry weight plant-1 followed by number of grains panicle-1, grain yield plant-1, biological yield plant-1, number of effective tillers plant-1 and flag leaf length. High heritability coupled with high genetic advance as per cent of mean was observed for grain yield plant-1, number of grains panicle-1, biological yield plant-1, root fresh weight plant-1 and root dry weight plant-1 indicating the presence of additive gene action. Grain yield plant-1 showed a highly significant and positive association with biological yield plant-1, harvest index percentage, root fresh weight plant-1, number of effective tillers plant-1 and 1000 seed weight. Path analysis revealed that biological yield plant-1 and harvest index percentage showed highest positive direct effect on grain yield plant-1. Furthermore, regression analysis revealed that biological yield plant-1, harvest index percentage, numbers effective of tillers plant-1, number of grains panicle-1, plant height and head rice recovery % as important traits contributing to grain yield plant-1. Therefore, phenotypic selection could be a viable approach for genetically improving these traits to obtain promising genotypes for future rice breeding programs.